Revisitando uma prática de formação à luz de referenciais freireanos: uma experiência com professores sem habilitação em Moçambique África - Antoniuk, Mariana (2015)
In developing countries such as Brazil and Mozambique, the lack of properly trained and licensed teachers is a serious issue. As such, there is an urgent need in these places to provide training for these educators, many of whom have never had access to a formal, quality education. The goal of this study is analyze one experience with untrained teachers and educators in Mozambique with Paulo Freire's concepts, in order to improve the quality of their teaching and, consequently, raise the level of education within the country. The study and y personal experience researching and coordinating three separate teacher-training projects in Mozambique during 2011, 2013, and 2014. Additionally, the study w y y developed by Paulo Freire (1970, 1977, 1997, 2003a, 2003b, 2011, 2014a, 2014b), as well as the writings of António Nóvoa (1995, 1997), Carlos Marcelo García (1999, 2009), and Vera Placco (2008). This study takes a qualitative j experience and fieldwork along with other early-childhood educators in Mozambique. The results and conclusions of this study demonstrate that the success of training teachers who have never been formally trained depends on the dialogue, as knowledge building process, on the respect the identity of each teacher and the critical reflection on his or her education methods